PENGARUH PREHEAT DAN TEMPERING TERHADAP KEKERASAN DAN STRUKTUR MIKRO HASIL PENGELASAN BAJA JIS SS 400 - Askar, Saiful; Sinarep, S.; Sari, Nasmi Herlina (Dinamika Teknik Mesin, 2013)
JIS steel SS 400 is one of the most common types of steel used for hot rolling steel structures general. This steel is excellented to the weldability and machinability properties. This study aimed to determine the effect of heat treatment with preheating without tempering (PTT), with preheating and tempering (PT), without preheating and without tempering (TPTT), and  without preheating tempering (TPT). The test results are then compared with the raw material specimens. Method of forming specimens using welding SMAW (Shielded Metal Arc Welding) DC reverse polarity using E7018 type electrode diameter of 4 mm. Type of seam used is V open seam with slit width and height of 2 mm and the width of the root angle 70o. This studied used a low alloy steel (JIS steel SS 400) which contain high levels of 0.20% C, maximum 0.005% S, maximum 0.005% P with repetitions each variation three times. Tests conducted it has testing the tensile strength, brinell hardness testing, and microstructure photo shoot. Value of the brinell hardness of welded joints highest in the tempering specimens without preheating, amounting with  163,911 HB hardness value. The structure of cementite and pearlite formed. While the lowest hardness values of specimens owned by raw material is 120,498 HB hardness values that form the microstructure of pearlite and ferrite.